1991
DOI: 10.1152/ajpregu.1991.261.3.r670
|View full text |Cite
|
Sign up to set email alerts
|

Circadian characteristics of Djungarian hamsters: effects of photoperiodic pretreatment and artificial selection

Abstract: Bidirectional artificial selection for (High Line) and against (Low Line) photoresponsiveness altered the percent of photoresponsive hamsters within lines and affected circadian function of hamsters identical in photoresponsiveness. For example, free-running period was shorter in responsive relative to nonresponsive hamsters. Between-line differences for responders and nonresponders were also found: hamsters from the High Line had a shorter free-running period relative to Low Line hamsters. However, phase angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 0 publications
1
42
1
Order By: Relevance
“…We preferred the Aschoff type II to the type I procedure (20) to generate a light PRC, since it eliminates possible confounding effects of chronic DD, including a more light-sensitive system compared with the LD cycle experiment (25)(26)(27)29) and permits simultaneous light stimulation (since all animals are entrained) at a given clock time. Using the type II procedure, we found that the response to light stimulation in PAC1 KO mice differed from our previously obtained results using the type I regime (11).…”
Section: Discussionmentioning
confidence: 99%
“…We preferred the Aschoff type II to the type I procedure (20) to generate a light PRC, since it eliminates possible confounding effects of chronic DD, including a more light-sensitive system compared with the LD cycle experiment (25)(26)(27)29) and permits simultaneous light stimulation (since all animals are entrained) at a given clock time. Using the type II procedure, we found that the response to light stimulation in PAC1 KO mice differed from our previously obtained results using the type I regime (11).…”
Section: Discussionmentioning
confidence: 99%
“…For species that exhibit strong reproductive seasonality (such as the Siberian hamster), however, LD 12:12 does not provide sufficient daily illumination to prevent reproductive inhibition. This was deemed to be an acceptable cost for the institution of a uniform LD cycle for all species, particularly because exposure to short photoperiods enhances (i.e., does not inhibit) circadian photoresponsiveness in Siberian hamsters [26].…”
Section: Methodsmentioning
confidence: 99%
“…By convention, the time of activity onset is designated as CT 0 for diurnal species and as CT 12 for nocturnal species. In order to achieve the largest expected phase delay of the activity rhythm, pulses were presented at CT 14 for Nile grass rats [30], laboratory rats [41], and Syrian hamsters [33], at CT 15 for degus [16] and Siberian hamsters [26], and at CT 16 for mice [18]. Because no phase-response curve has been published for Mongolian gerbils, CT 15 was chosen as a tentative optimal circadian time for this species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In temperate zones, the photoperiod markedly changes across seasons and affects mammalian physiology and behaviour (Sumova et al, 2004). For instance, in nocturnal rodents, the duration of locomotor activity reflects the photoperiod as being shorter on long summer than on -E-mail: giuseppe.piccione@unime.it short winter days (Puchalski and Lynch, 1991;Elliott and Tamarkin, 1994). The rhythmic production of the pineal hormone melatonin, which is a part of the timekeeping system, is also highly photoperiod-dependent, both in nocturnal and in diurnal animals; the high nocturnal melatonin production is shorter on long summer than on short winter days (Illnerová , 1991).…”
Section: Introductionmentioning
confidence: 99%